If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 9y + -3 = 7y + 43 + -4y Reorder the terms: 4 + -3 + 9y = 7y + 43 + -4y Combine like terms: 4 + -3 = 1 1 + 9y = 7y + 43 + -4y Reorder the terms: 1 + 9y = 43 + 7y + -4y Combine like terms: 7y + -4y = 3y 1 + 9y = 43 + 3y Solving 1 + 9y = 43 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 1 + 9y + -3y = 43 + 3y + -3y Combine like terms: 9y + -3y = 6y 1 + 6y = 43 + 3y + -3y Combine like terms: 3y + -3y = 0 1 + 6y = 43 + 0 1 + 6y = 43 Add '-1' to each side of the equation. 1 + -1 + 6y = 43 + -1 Combine like terms: 1 + -1 = 0 0 + 6y = 43 + -1 6y = 43 + -1 Combine like terms: 43 + -1 = 42 6y = 42 Divide each side by '6'. y = 7 Simplifying y = 7
| 729p^2-36= | | .49x^2+12x=20 | | 15+10x+x^2=0 | | -21/4(-10)+80 | | 2h+1=-17 | | -10=10a | | 18x-12=22x+8 | | 3k=-12 | | 8-5x=-22 | | 8-5x=-22 | | 12.5*n=100 | | 4x^3-9x^2-x-6=0 | | -21/4(-10) | | 31=-7+x | | -21/4(10) | | 2(x+22)=5+3(x-2)-4x | | -3x8+4/(-2) | | r-45=-45 | | 9g+11=-2 | | 4xy^2+44x^2y^2-28xy^2=0 | | 3/4w=-16/27 | | 3/4s=-16/27 | | -16t^2+16=0 | | ab-9a+4b-36= | | -5(-3u+7)-3u=6(u-6)-7 | | -3=k+2 | | 2/3(1/8+4x)-3/8=5/8 | | 3a(x+7y)-b(x+7y)= | | s/3=5 | | 35ab-21ab^2= | | j-8=9 | | X/7=84 |